Diet and medical foods in Parkinson’s disease - Klaus W. Lange; Yukiko Nakamura; Ning Chen; Jianjun Guo; Shigehiko Kanaya; Katharina M. Lange; Shiming Li (Food Science and Human Wellness)
Parkinson's disease (PD) is a slowly progressive neurodegenerative disorder with motor and non-motor signs, which begins long before the diagnosis can be made. Pharmacotherapy with dopaminergic drugs is the mainstay of PD therapy. There is no currently available cure or disease-modifying treatment. Diet and various foods have been proposed as possible risk factors for PD. Nutritional supplementation with omega-3 fatty acids, vitamin D, B vitamins, and coenzyme Q may have potential in the management of PD. In addition, several strategies could possibly lead to the development of medical foods in PD. For example, ketogenic diets may have effects complementary to pharmacotherapy. Gut microbial dysbiosis and altered microbial metabolites found in PD may lead to chronic low-grade inflammation in gut and brain. Interventions targeting gut microbiota, such as the supplementation of probiotics, may provide novel approaches to PD in regard to both symptomatic treatment and disease modification. High quality randomized controlled trials need to be conducted in order to evaluate whether these food-based strategies have symptomatic efficacy or the potential to delay the progression of PD. Keywords: Parkinson's disease, Diet, Medical food, Ketogenic diet, Probiotics, Prevention